SAT0443 In Vitro Effects of Canakinumab on Human Osteoarthritic Chondrocytes. (10th June 2014) - Cheleschi, S.; Cantarini, L.; Pascarelli, N.A.; Lucherini, O.M.; Guidelli, G.M.; Collodel, G.; Galeazzi, M.; Fioravanti, A.
Abstract : Background: Canakinumab is a human IgGκ monoclonal antibody targeting Interleukin (IL)-1β; its action involves the neutralization of the signaling of IL-1β, the most important cytokine in the pathogenesis of Osteoartrhitis (OA). In response to IL-1β, chondrocytes secrete other proinflammatory cytokines, neutral metalloproteinases (MMPs), nitric oxide (NO); furthermore IL-1β inhibits chondrocytes proliferation and induces apoptosis. Objectives: The aim of our study was to evaluate the possible in vitro effects of canakinumab on human OA chondrocytes cultures cultivated in the presence or absence of tumor necrosis factor (TNF)-α. Methods: Chondrocytes, from femoral cartilage of five OA patients who underwent surgery for hip prostheses, were isolated using sequential enzymatic digestion. Primary cultures so obtained were incubated with canakinumab (1μg/ml and 10μg/ml) alone or with TNF-α (10ng/ml). We evaluated after 48h cell viability, release of proteoglycans (PG) and NO in culture medium, inducible nitric oxide synthase (iNOS) and MMP-1, 3, 13 expression, the percentage of apoptosis and necrosis. After 24h we performed IL-1β dosage (ELISA). Finally, we used a transmission electron microscope (TEM) for morphological assessment. Results: Canakinumab alone at the two concentrations studied hadn't cytotoxic effect and didn't modify significantly IL-1β levels in the culture medium. TNF-α caused a significant decrease of the percentage of viable cell (P<0.001) and a significant increase of IL-1β. Both concentrations of canakinumab significantly restored the cell viability and reduced IL-1β production in TNF-α stimulated chondrocytes. No significant modification of PG levels was observed in the cultures treated with canakinumab alone; TNF-α determined a significant decrease (P<0.001) in PG levels restored by canakinumab in a significant dose-dependent manner. Incubation of chondrocytes with canakinumab alone didn't affect nitrite release; TNF-α induced a significant increase (P<0.001) in NO production that was significantly (P<0.01) reduced after co-incubation with TNF-α and canakinumab at two concentrations used. The data of the NO were confirmed by the immunocytochemistry assay for iNOS. TNF-α stimulated chondrocytes displayed a significant increase of MMP-1, 3, 13 gene expression; a significant reduction was shown after co-treatment with TNF-α and canakinumab. Our experiments confirmed the pro-apoptotic effect of TNF-α and demonstrated a protective role of canakinumab at two concentrations examined. The biochemical results were further confirmed by TEM. Conclusions: It is generally accepted that IL-1β and TNF-α are the pivotal cytokines involved in OA physiopathology. Hence, the neutralization of these cytokines appears to be a logical development for OA therapy. In the present study we showed, for the first time, that canakinumab counteracts the negative effect of TNF-α on OA chondrocyte cultures, probably inhibiting IL-1β signaling. References: Dhimolea E. Mabs 2010;2:3-13. Fioravanti et al. J Pharmacol Sci 2012;20:6-14. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5066